Stereotactic Radiosurgery for Cavernous Sinus Versus Noncavernous Sinus Dural Arteriovenous Fistulas: Outcomes and Outcome Predictors - Hung, Yi-Chieh; Mohammed, Nasser; Kearns, Kathryn N; Chen, Ching-Jen; Starke, Robert M; Kano, Hideyuki; Lee, John; Mathieu, David; Kaufmann, Anthony M; Wang, Wei Gang; Grills, Inga S; Cifarelli, Christopher P; et al. (Neurosurgery, 2020)
BACKGROUND: Dural arteriovenous fistulas (DAVFs) can be categorized based on location. OBJECTIVE: To compare stereotactic radiosurgery (SRS) outcomes between cavernous sinus (CS) and non-CS DAVFs and to identify respective outcome predictors. METHODS: This is a retrospective study of DAVFs treated with SRS between 1988 and 2016 at 10 institutions. Patients' variables, DAVF characters, and SRS parameters were included for analyses. Favorable clinical outcome was defined as angiography-confirmed obliteration without radiological radiation-induced changes (RIC) or post-SRS hemorrhage. Other outcomes were DAVFs obliteration and adverse events (including RIC, symptomatic RIC, and post-SRS hemorrhage). RESULTS: The overall study cohort comprised 131 patients, including 20 patients with CS DAVFs (15%) and 111 patients with non-CS DAVFs (85%). Rates of favorable clinical outcome were comparable between the 2 groups (45% vs 37%, P = .824). Obliteration rate after SRS was higher in the CS DAVFs group, even adjusted for baseline difference (OR = 4.189, P = .044). Predictors of favorable clinical outcome included higher maximum dose (P = .014) for CS DAVFs. Symptomatic improvement was associated with obliteration in non-CS DAVFs (P = .005), but symptoms improved regardless of whether obliteration was confirmed in CS DAVFs. Non-CS DAVFs patients with adverse events after SRS were more likely to be male (P = .020), multiple arterial feeding fistulas (P = .018), and lower maximum dose (P = .041). CONCLUSION: After SRS, CS DAVFs are more likely to obliterate than non-CS ones. Because these 2 groups have different total predictors for clinical and radiologic outcomes after SRS, they should be considered as different entities.
Keywords: senioři; Predictor; Intracranial; Retrospective Studies; Central Nervous System Vascular Malformations; Prognosis; Cohort Studies; výsledek terapie; Middle Aged; Gamma Knife; mužské pohlaví; Adult; cévní malformace centrálního nervového systému; Radiosurgery; Dural arteriovenous fistulas; kohortové studie; ženské pohlaví; prognóza; retrospektivní studie; Humans; Cavernous sinus; lidé středního věku; Cavernous Sinus; dospělí; sinus cavernosus; Female; Aged; Treatment Outcome; radiochirurgie; lidé; Male